Penerapan Kebijakan Penanganan Konflik dalam Meningkatkan Produktivitas Kerja - Nur Azizah Aulia, Annisa; Hidayat, Wahyu (NIẒĀMUL`ILMI : Jurnal Manajemen Pendidikan Islam, 2024)
A good Conflict Management Policy is a benchmark for successful work productivity. Work productivity is a collection of various tasks to achieve educational goals. This study aims to find out how the application of conflict management policies in increasing work productivity at MTs Plus Darul Hufadz. The method used in this study uses a qualitative descriptive method, which is a strategy to examine and find out the meaning of groups or individuals related to social problems. In research, it includes discussions and visible processes, analyzes materials and data in an inductive way, builds them from specific things to general things, and researchers make shapes regarding the meaning of the data in question. The results of the study show that the Application of Conflict Management Policies in Increasing Work Productivity at MTs Plus Darul Hufadz can have a positive impact. With effective policies in place, conflicts between staff and school members can be resolved in a constructive way, creating a harmonious and collaborative work environment.